Ammonium removal from aqueous solution by ion-exchange using packed bed natural zeolite - Demir, A; Günay, A; Debik, E (WATER RESEARCH COMMISSION, 2002)
Ammonium removal from aqueous solution by a natural ion-exchange resin was investigated by considering the factors affecting the ammonium-exchange capacity including the zeolites' particle size, the loading flow rates and the impact of a number of regenerations upon the ion-exchange capacity. The resin column was exhausted by downflow at 10, 25, 50 and 75 bed volume (BV)/h until effluent ammonium concentration of more than 10 mg/lNH(4)(+) was achieved. The results indicate that conditioning of the zeolite improves the ion-exchange capacity and that the smaller particle size also causes a higher ion-exchange capacity due to greater available surface area. The actual ion-exchange capacity of the conditioned fine (1.00+0.125) and coarse (-2.00+1.00) mm clinoptilolite was found to be 0.57 and 0.38 meq/g zeolite, respectively.
Keywords: CLINOPTILOLITE; WASTEWATERS; WATER; Water Resources